Digital service quality and mobile banking continuity as drivers of loyalty and bank reputation - Rahardjo, Irbawanti Pungky; Darma, Emile Satia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to test and obtain empirical evidence of the effect of online service quality measurement scales in the banking sector environment in increasing Continuity of Mobile Banking Service Usage, and can increase customer loyalty and bank reputation. Design/Methodology/Approach: This research is a quantitative study using primary data distributed to Bank Negara Indonesia (BNI) customers as many as 387 respondents were obtained. The data obtained was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) model. Research findings: The results obtained that Application architecture and user friendliness cannot increase Continuity of Mobile Banking Service Usage. The measurement scale for online service quality in the banking sector that can increase Continuity of Mobile Banking Service Usage is Application efficiency, Reliability, Responsiveness, Security, and Familiarity. And Continuity of Mobile Banking Service Usage can increase customues loyalty and bank reputation. Theoretical contribution/Originality: This research confirms the Theory of Planned Behavior, this research tests the measurement scale of online service quality in the banking sector environment in order to maintain the existence of banks.Practitioner/Policy implication: The results of this study contribute to the banking sector in improving online service quality, especially in a dynamic environment.